2004
DOI: 10.1086/386287
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Varying Concentrations ofClostridium difficileToxin A on Epithelial Barrier Function and Expression of Cytokines

Abstract: In C. difficile infection, the development and severity of colonic inflammation may depend on the exposure of intestinal epithelial cells to toxins and the expression of proinflammatory (IL-8) and protective (TGF-beta) factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 37 publications
2
46
0
Order By: Relevance
“…For both of these cell types, significant cytotoxicity is seen only after exposure to 10 ng or more of toxin A per ml. However, at concentrations of Ͻ10 ng/ml, there is a loss of transepithelial resistance (23,34), and the cells are induced to express transforming growth factor ␤ (23). These findings support the concept that there are distinct intracellular mechanisms by which C. difficile toxin A mediates its effects on host cells (17,21,24,34,50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For both of these cell types, significant cytotoxicity is seen only after exposure to 10 ng or more of toxin A per ml. However, at concentrations of Ͻ10 ng/ml, there is a loss of transepithelial resistance (23,34), and the cells are induced to express transforming growth factor ␤ (23). These findings support the concept that there are distinct intracellular mechanisms by which C. difficile toxin A mediates its effects on host cells (17,21,24,34,50).…”
Section: Discussionmentioning
confidence: 99%
“…Although local concentrations at the intestinal epithelial surface may not be accurately reflected by the concentrations present in a stool sample, one can postulate the in vivo significance of an in vitro response by host cells to different concentrations of the toxin. Exposure to low concentrations of toxin A induces expression of the anti-inflammatory cytokine transforming growth factor ␤ and much slower loss of epithelial barrier function (23). By contrast, high concentrations of toxin readily overcome the epithelial barrier and induce the expression of proinflammatory cytokines, such as tumor necrosis factor alpha and interleukin-8 (14,21,38) in lamina propria monocytes/macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…infection by one case study 16 ; and with a higher incidence of Clostridium difficile infection 17 ; whereas animal models have proven the role of specific enteric bacteria ( E. coli ENT CAI:5) in the gluten-induced immunopathology. 18 Interestingly, some of these pathogenic bacteria previosly associated with the disease can produce toxins that disrupt the tight junction proteins and increase the intestinal permeability, 19-22 a condition linked to the break-down of gluten tolerance. 1 Although some potential candidates have been proposed, we lack strong evidence for pathogenic bacteria as trigger factors for CD development in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In intact monolayers of carcinoma-derived intestinal epithelial cell lines in vitro, apically applied toxin A induces injury and loss of barrier function (43,45). Other early responses by intestinal epithelial cells exposed to toxin A include changes in the cytoskeleton (10,15) and secretion of cytokines, such as transforming growth factor beta (TGF-␤) (20) and interleukin-8 (5,13,26), before the cells undergo programmed cell death (6,26). Our previous studies have shown that primary human intestinal epithelial cells, monocytes, and intestinal macrophages are more sensitive than lymphocytes to C. difficile toxin A-induced cell death (25,26,42).…”
mentioning
confidence: 99%
“…In view of their capacity to secrete a number of cytokines and to interact with other cell populations (36), intestinal myofibroblasts are also believed to be key players in inflammatory responses in the intestine (1,9,12,22). They have been shown to provide protection to intestinal epithelial monolayers against loss of barrier function in response to low concentrations of toxin A, via secretion of TGF-␤ (20). Following injury and loss of toxin-exposed epithelial cells in vivo, myofibroblasts, which are capable of migrating onto the surface of the basement membrane (24), would be expected to be exposed to C. difficile toxins.…”
mentioning
confidence: 99%